Self-Employment and Protection from Mobbing and Discrimination - Barański, Michał; Mądrzycki, Błażej (Acta Universitatis Lodziensis. Folia Iuridica, 2022)
Work under civil law contracts has become increasingly popular in recent years. Primarily young people (entering the labour market) are employed based on civil law contracts. A similar phenomenon is a gainful activity within the so-called self-employment under conditions of economic dependence on one’s contractor. Awareness of the dissemination of non-employment forms of employment has led the authors to consider possible forms of protection against mobbing and discrimination in the case of self-employment. These phenomena (mobbing and discrimination) are generally associated with the relationship between employer and employee. However, the mere fact of a different type of employment does not exclude the risk of ‘mobbing’ or discrimination. In such circumstances, it is almost natural to explore possible forms of protection. The authors have analysed the existing legal regulations in search of available solutions that can provide adequate protection for the self-employed.